2021
DOI: 10.1108/imefm-06-2020-0269
|View full text |Cite
|
Sign up to set email alerts
|

The effects of corporate disclosure on firm value and firm performance: evidence from Turkey

Abstract: Purpose The purpose of this study is to investigate the effects of firms’ disclosure practices on firm value and firm performance. Design/methodology/approach Firms’ disclosure scores were calculated based on unique hand-collected data by using the S&P transparency and disclosure index (S&P TD index). Ordinary least squares with year/firm fixed effects and two-stage least square methods were used to test the hypothesis. Findings It is observed that firms’ disclosure scores have positive and statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 63 publications
4
24
0
1
Order By: Relevance
“…Bae et al (2018) found that reducing information asymmetry could maintain a competitive advantage for the firm. Some studies found that firm VD has a positive and statistically significant effect on firm value (Assidi, 2020;Temiz, 2021). Based on the above discussion, the current study proposes the following hypotheses: H1.…”
Section: Theoriesmentioning
confidence: 75%
“…Bae et al (2018) found that reducing information asymmetry could maintain a competitive advantage for the firm. Some studies found that firm VD has a positive and statistically significant effect on firm value (Assidi, 2020;Temiz, 2021). Based on the above discussion, the current study proposes the following hypotheses: H1.…”
Section: Theoriesmentioning
confidence: 75%
“…Secondly, application of CG guidelines reduces the level of asymmetric information by making firms disclose voluntarily, leading to higher investor confidence and lower Ke. Therefore, firms will gradually increase their VD given its benefits with asymmetric information and positively influence firm value (Temiz, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Corporate disclosure helps build trust, improves market liquidity, increases demand for corporate stocks and helps contain transaction cost that leads to lower Ke (Botosan and Plumlee, 2002; Leuz and Verrecchia, 2005; Temiz, 2021). Corporate governance (CG) includes standards, norms and practices that are disclosed to limit asymmetric information, which may also result in low external management cost (Srivastava et al , 2019) and cost of capital (Chen et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to Saygili et al (2021); Rawal et al (2022), Furthermore, Zaman et al (2018) identified voluntary disclosure as one of the corporate governance strategies that can improve operating performance. Temiz (2021) found no link between transparency and financial performance; however, Ararat et al ( 2017 Based on the agency theory, CG is a significant strategic practise in minimising agency difficulties such as agent opportunism, information asymmetry, and divergent attitudes of agents and other stakeholders toward risks and agency costs to improve financial performance (Salem, 2019;Shaji & Shajahan, 2020;He, 2021), as well as depending on the Resource Dependence Theory (RDT), which indicates that an organization's performance is influenced by its resources. In light of the contradictory findings about the impact of Transparency and disclosure on financial performance, the following hypothesis is proposed in this paper: Hypothesis 3 (H3).…”
Section: Transparency and Disclosure And Financial Performancementioning
confidence: 99%